2019
DOI: 10.1021/acs.iecr.9b05183
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Palladium(II) and Rhodium(III) Using a Polymer Inclusion Membrane Containing a Phosphonium-Based Ionic Liquid Carrier

Abstract: In this study, we report the separation of Pd(II) and Rh(III) in a chloride solution using a polymer inclusion membrane (PIM). We designed a trioctyl(dodecyl) phosphonium chloride (P 88812 Cl) ionic liquid as a metal carrier for the PIM separation system. The effects of PIM composition and experimental conditions were systematically investigated. The concentrations of hydrochloric acid in the feed solution and thiourea in the receiving solution were found to play a crucial role in the success of selective sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Subsequently, we expanded the application of the ionic liquid to PIM technology with the aim of creating a simpler, cheaper, and more environmentally friendly process. As recently reported, a stable PIM for selective separation of Pd­(II) and Rh­(III) was successfully fabricated by incorporating the P 88812 Cl ionic liquid carrier into a poly­(vinylidene fluoride- co -hexafluoropropyle) (PVDF- co -HFP) polymer base with a small amount of 2-nitrophenyloctyl ether (2NPOE) as a plasticizer . In the current study, we aimed to demonstrate a complete process for PGM mutual separation using the PIM transport system.…”
Section: Introductionmentioning
confidence: 97%
“…Subsequently, we expanded the application of the ionic liquid to PIM technology with the aim of creating a simpler, cheaper, and more environmentally friendly process. As recently reported, a stable PIM for selective separation of Pd­(II) and Rh­(III) was successfully fabricated by incorporating the P 88812 Cl ionic liquid carrier into a poly­(vinylidene fluoride- co -hexafluoropropyle) (PVDF- co -HFP) polymer base with a small amount of 2-nitrophenyloctyl ether (2NPOE) as a plasticizer . In the current study, we aimed to demonstrate a complete process for PGM mutual separation using the PIM transport system.…”
Section: Introductionmentioning
confidence: 97%
“…A PIM FTIR examination before and after 7-day immersion in 10 mol L −1 HCl exhibited the characteristic functional groups of PVDF-HFP and P66614Cl in the PIM before and after immersion. These spectra indicated the absence of PIM structural changes before and after immersion in a highly acidic solution, which also revealed the stable performance of PVDF-HFP-based PIMs containing P66614Cl for the separation of Pd(II) [68]. In separate research, the same authors reported a selective separation of PGMs using PVDF-HFP-based PIMs containing a newly synthesized P88812Cl ionic liquid as the extractant [69].…”
Section: ■ Pims Prepared Using Co-polymersmentioning
confidence: 85%
“…Moreover, ionic liquids are commonly employed in the separation processes to remove noble metal ions from aqueous solution (e.g., Cyphos IL 101 is a good extractant of palladium, silver, platinum, and gold ion solvent extraction). Fajar et al used a trioctyl(dodecyl) phosphonium chloride (P 88812 Cl) ionic liquid as an ion carrier in polymer inclusion membrane for the removal of Pd(II) ions with an efficiency of 98% [44]. Boudessocque et al applied ionic liquids bearing tetrahexylammonium and tetraoctylammonium cations and halide, dicyanamide, thiocyanato, and bis(trifluoromethysulfonyl)imide in the solvent extraction process for removal of Au(III) and Pt(II) ions (efficiency above 90%) [45].…”
Section: Discussionmentioning
confidence: 99%